Older red cell units are associated with an increased incidence of infection in chronically transfused adults with sickle cell disease. Issue 3 (June 2017) - Karafin, Matthew S.; Carpenter, Erica; Pan, Amy; Simpson, Pippa; Field, Joshua J.
Abstract: Background: In adults with sickle cell disease (SCD), the effects of the red cell storage lesion are not well defined. The objectives of this study were to: (1) describe the distribution of storage ages provided to adults with SCD, and (2) evaluate clinical outcomes associated with storage age. Patients and methods: We performed a retrospective cohort study of adults with SCD managed with prophylactic simple transfusion regimens. Units were universally pre-storage leukocyte reduced and CEK-matched. Age of the unit was 42 days minus the difference between the expiration and transfusion dates. A mixed effects model, which accounts for a subject's contribution to repeated transfusion encounters, was used to investigate the association between storage age and the incidence of hospital encounters for infection and pain crises prior to the next red cell transfusion. Results: Over the study interval, twenty-eight steady-state adults with SCD received 627 units via simple transfusion over 281 outpatient encounters. Overall median unit storage age was 22 days (range: 2–42 days). Receipt of older units was associated with an increased incidence of emergency department or hospital admission for infection prior to the next transfusion ( p  = 0.04). There was no association between unit storage age and admission for pain ( p  = 0.4). Discussion: In a cohort of chronically transfused adults with SCD, we provide evidence that receipt of older units is associated with a higher rate of admission for infection. Prospective studies will need to validate these data and explore potential mechanisms by which these older units promote infection.